Effect of Silver Nanoparticles on Fluorescence Spectra of C480 dye - AL-Awadi, Sarmed S.; Shbeeb, Ruwaida T.; Chiad, Bahaa T. (Iraqi Journal of Science, 2018)
This work aim to study the effect of silver nanoparticles on fluorescence intensity of Coumarin 480 dye by using the sandwiches technique where AgNP layer had been separated from C480 layer by different type of materials such as silica, PMMA polymer and PVA polymer layer. Silver nanoparticles had been prepared by the chemical reduction method so the AgNP layer coating had been done by hot rotation liquid method. The optical properties of prepared samples had been tested by using UV-VIS absorption spectrophotometer and Fluorescence spectrophotometer. Morphology, average size and the structure of nanoparticles were estimated using AFM, SEM testes